2021
DOI: 10.3390/cancers13184514
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Experience with Trifluridine/Tipiracil for Refractory Metastatic Colorectal Cancer: The ROS Study

Abstract: Trifluridine/tipiracil is currently approved for metastatic colorectal cancer (mCRC) refractory to available therapies. However, there is no consensus on factors that predict treatment outcomes in daily practice. We assessed the early clinical experience with trifluridine/tipiracil in Spain and potential survival markers. This was a retrospective cohort study of mCRC patients who participated in the trifluridine/tipiracil early clinical experience programme in Spain. The primary outcome was overall survival (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 28 publications
0
17
1
Order By: Relevance
“…Interestingly, in contrast to the data reported in the pivotal RECOURSE trial, where no differences were observed between age subgroups (7.1 months in patients <70 years vs 7.0 months in patients ≥70 years), in TACTIC there was a slight OS benefit observed in older patients (8.6 months) as compared to young and intermediate age patients (7.4 and 6.8 months, respectively) 9 . These findings suggest that low metastatic burden and indolent disease as well as older age may be considered not only as favorable prognostic factors but also as predictive factors for survival and preservation of ECOG PS in patients with pretreated mCRC receiving FTD/TPI in routine clinical practice, bearing in mind the limited comparability between real‐world and clinical trial data as reported previously 26,27 . Moreover, patients with BPC or GPC may maintain a good general condition and performance status for a longer period of time as compared to patients with PPC.…”
Section: Discussioncontrasting
confidence: 73%
“…Interestingly, in contrast to the data reported in the pivotal RECOURSE trial, where no differences were observed between age subgroups (7.1 months in patients <70 years vs 7.0 months in patients ≥70 years), in TACTIC there was a slight OS benefit observed in older patients (8.6 months) as compared to young and intermediate age patients (7.4 and 6.8 months, respectively) 9 . These findings suggest that low metastatic burden and indolent disease as well as older age may be considered not only as favorable prognostic factors but also as predictive factors for survival and preservation of ECOG PS in patients with pretreated mCRC receiving FTD/TPI in routine clinical practice, bearing in mind the limited comparability between real‐world and clinical trial data as reported previously 26,27 . Moreover, patients with BPC or GPC may maintain a good general condition and performance status for a longer period of time as compared to patients with PPC.…”
Section: Discussioncontrasting
confidence: 73%
“…In a cohort of 379 metastatic colorectal cancer patients who received trifluridine/tipiracil mostly as a third or later-line treatment in the Spanish multicenter ROS study, the median OS was 7.9 months [ 35 ]. Patients with a maximum of two metastatic sites, without liver metastases, with alkaline phosphatase less than 300 IU and with a neutrophil-to-lymphocyte ratio of less than five had a significantly longer OS than patients with three or more metastatic sites, liver metastases, alkaline phosphatase levels above 300 IU and a neutrophil-to-lymphocyte ratio above five [ 35 ].…”
Section: Clinical Biomarkersmentioning
confidence: 99%
“…Grade 2 and higher neutropenia and higher CEA levels were independent prognostic factors for OS. Patients in the ROS study who had trifluridine/tipiracil dose reductions, presumably due to neutropenia, had a longer OS than that of patients who did not need a dose reduction [ 35 ].…”
Section: Biomarkers From the Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lattanzi et al found that NLR was associated with 30-day mortality and morbidity after intracerebral hemorrhage, which could improve outcome prediction of acute intracerebral hemorrhage (11). They also played an important role in the prognosis of acute ischemic stroke patients undergoing revascularization treatment (12,13), and had a certain predictive value in the occurrence, efficacy, and prognosis of tumors (14)(15)(16). The above evidence shows the significance and broad potential of serum biomarkers that are easy to obtain and inexpensive in daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%